Studies in Health Technology and Informatics Volume 19 - Medical Imaging Analysis of Multimodality 2D/3D Images - Beolchi, L. (IOS Press, 2014)
Health Telematics (formerly AIM: Advanced Informatics in Medicine) is a subprogram under the European Community R&TD programme "Telematics in Areas of General Interest". It started as an Exploratory Action in 1988 and continued on a larger scale in 1990 to run through 1994 with the unifying objective: "To develop tools, techniques and practices supporting a common European approach to health care informatics and telecommunications." The shift in name from AIM to "Health Telematics" indicates a significant change in the direction of building upon the interconnectivity of digital workstations and data communication. Under the new name the Subprogram is appearing also in the 4th Framework Program (1995-1998). The programme supports research and development activities by two mechanisms. One is the normal one of funding consortia successfully bidding in open calls against task descriptions with up to 50 % of the cost of the project. Around 45 projects were financed this way during the 3rd Framework Program. The other one is supporting concerted actions aiming at obtaining European added value from bringing nationally funded research and researchers together. Around 10 such actions are on-going, mostly to disseminate information provide teaching elements, and bring end-users together. User acceptability and legal/regulatory issues are all high on the agenda.